Selection of membranes and reagents for membrane facilities operation to treat ground water - Vladimir A. Golovesov (Vestnik MGSU, 2020)
Introduction. New techniques to operate reverse osmosis facilities are presented as well as problems and disadvantages are discussed that vodocanals face with, such as: imported chemicals, high operational costs, low reliability, concentrate handling and disposal. Main reasons that cause problems are understood. Experiments are described that provide evaluation of reagents efficiencies and ways to significantly decrease concentrate flows and reduce operational costs. A newly developed approach is presented that uses nanofiltration membranes and enables us to reduce chemical, energy and concentrate discharge costs. Goals — the investigation of antiscaling efficiencies together with use of membranes with different properties to reduce operational costs due to low chemical dosing, low pressure and energy consumption. Materials and methods. Experiments are conducted to evaluate inhibiting efficiencies using different antiscalant doses and different membranes. Experimental method is describe to calculate rates of calcium carbonate formation as a function of coefficient K (Initial Volume Reduction coefficient) value. To provide economical comparison of different water treatment techniques, operational costs are evaluated depending on operational parameters, such as: coefficient K, working pressure antiscalant dose values as well as membrane type used. Results. Main relationships are obtained of calcium carbonate scaling rates that provide chemical consumption, concentrate flow rate and power consumption. Using two ground water compositions examples are calculated to predict product water composition for different membranes and of feed water and product water flows. Operational costs are calculated for both cases. Conclusions. To reduce hardness of the ground water nanofiltration membranes can be efficiently applied that ensures low operational costs of membrane facility. Application of nanofiltration membranes possess lower scaling propensities and therefore enables us to use smaller doses of aniscalants added to feed water. Despite the increased amount of membrane elements required to furnish membrane facility, the total operational costs amount is lower due to lower chemical costs (antiscalants and cleaning agents), energy costs as well as payments for concentrate disposal.